ATTRACTION DIRECTIONS OF FOREIGN INVESTMENTS IN TERMS OF INVESTMENT ENVIRONMENT ATTRACTIVENESS - Tirkashev Farruxjon Khоlyigitovich (American Journals, 2025)
The article analyzes the main directions of attracting foreign investments based on the concept of investment environment attractiveness. Investment environment attractiveness is a set of factors that determine a country’s or region’s potential to attract investors. The study examines how economic, political, legal, social, and infrastructural factors affect investment attractiveness. Additionally, it considers incentives created for foreign investors, free economic zones, tax benefits, and government support mechanisms.
Keywords: Investment environment, investment attractiveness, foreign investments, attracting investments, free economic zones, tax incentives, public-private partnership, innovation, export, economic policy, infrastructure, investors, investment strategy, economic development, international experience, investment policy.